Olive oil inhibits DMH-induced colon tumor growth by triggering mitochondrial apoptotic pathway: An in vivo study. Issue 6 (2018) - Nanda, N; Mahmood, S; Mahmood, A; Bhat, M Owais; Dhawan, DK
No abstract available